Strong dependence of flattening and decoupling of graphene on metals on the local distribution of intercalated oxygen atoms. (May 2016) - Romero-Muñiz, C.; Martín-Recio, A.; Pou, P.; Gómez-Rodríguez, J.M.; Pérez, Rubén
Abstract: We show that the flattening of a highly corrugated graphene layer grown on Rh(111) is linked to its decoupling from the metal substrate taking place during oxygen intercalation in the lowest moiré sites. We have been able to track this process at the atomic scale by combining scanning tunneling microscopy experiments and first-principles calculations. Initially, intercalated and non intercalated areas can coexist through a careful experimental control of the oxygen dosage and temperature. This allows a direct comparison of the corrugation profiles of both areas. Although the corrugation increases for very low coverages, higher oxygen concentrations provoke the occupation of the lowest moiré sites leading to a flattening of the graphene sheet. This mechanism is confirmed by calculations of the equilibrium geometries for different oxygen concentrations. Electronic structure calculations and scanning tunneling spectroscopy measurements reveal that the flattening of the graphene layer is linked with the local uncoupling from the metal induced by the increasing oxygen concentration. This process, completed only when the lowest moiré sites are filled with oxygen, finally converts a strongly coupled system into a free-standing like p-doped graphene layer.